2018
DOI: 10.1111/jasp.12506
|View full text |Cite
|
Sign up to set email alerts
|

The effects of “phubbing” on social interaction

Abstract: This research experimentally investigated the social consequences of “phubbing” – the act of snubbing someone in a social setting by concentrating on one's mobile phone. Participants viewed a three‐minute animation in which they imagined themselves as part of a dyadic conversation. Their communication partner either phubbed them extensively, partially, or not at all. Results revealed that increased phubbing significantly and negatively affected perceived communication quality and relationship satisfaction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
254
1
31

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 313 publications
(384 citation statements)
references
References 38 publications
27
254
1
31
Order By: Relevance
“…Phubbing partners have been found to lower relationship satisfaction (McDaniel & Coyne, ). Chotpitayasunondh and Douglas () have also found that phubbing decreases relationship satisfaction. The inverse relationship between partner phubbing and relationship satisfaction was not only reported by American participants (Roberts & David, ) but also by Chinese participants (X. Wang et al, ).…”
Section: Impactsmentioning
confidence: 88%
See 4 more Smart Citations
“…Phubbing partners have been found to lower relationship satisfaction (McDaniel & Coyne, ). Chotpitayasunondh and Douglas () have also found that phubbing decreases relationship satisfaction. The inverse relationship between partner phubbing and relationship satisfaction was not only reported by American participants (Roberts & David, ) but also by Chinese participants (X. Wang et al, ).…”
Section: Impactsmentioning
confidence: 88%
“…It is evident that phubbing behavior is an increasingly normalized occurrence in social interactions, which has both immediate and long‐term negative implications, such as poorer conversation quality and weaker interpersonal connections (Chotpitayasunondh & Douglas, ; Nakamura, ; Vanden Abeele et al, ), alongside reduced relationship satisfaction and depression (Halpern & Katz, ; Roberts & David, ; X. Wang et al, ). The prevalence of phubbing behavior and its negative impacts makes it necessary to continue to research what drives such behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations